Natural selection and evolution of behaviour and its variability in experimental populations - Afonso, Bruno Alexandre Caetano (2019)
Behaviour has evolved in animal species as an output from the function of energetically expensive nervous systems. Notwithstanding, the ability to perform behaviour seems to have persisted in animal species until today, hence behaviour in general might have a significant adaptive value. Such value has been demonstrated experimentally in some instances.(...)